SARAPAN SEHAT MENUJU GENERASI SEHAT BERPRESTASI - Sitoayu, Laras; Wahyuni, Yulia; Angkasa, Dudung; Noviyanti, Anugrah (Universitas Esa Unggul, 2016)
AbstractGood food for school children is a food that contains many varieties and in accordance with the recommended dietary allowance, one through breakfast habit. In fact, not all school children have breakfast habits. Only 10.6% of the children breakfast sufficient energy (>30%) and still very lack of breakfast with diverse food. Breakfast habit is important not only taught at home, but also need to be socialized at school. Teacher, as parent in the school need to understand the importance of a healthy breakfast habit and are able expected to socialize. This activity is one of the implementation of the Circular of Kementerian Dalam Negeri No. 444/1123/ PMD dated 4 February 2013 to the Governor throughout Indonesia, to support and implement the Week Breakfast National or Pekan Sarapan Nasional (PESAN) with campaigning and encouraging people to adopt a healthy breakfast behave through seminars. This event aims to disseminate a healthy breakfast for any teacher PAUD/ kindergarten for a whole West Jakarta through seminars, conducted in Ballroom Kemala Esa Unggul University. Socialization is done with providing counselling and using comics